Síntese de óxidos Ni1-xCuxWO4 tipo wolframatos por coprecipitação e precipitação química - Fernandes, Luiz Carlos (Universidade Federal Rural do Semi-Árido, 2018)
Ceramic pigments stand out due to their optical properties that are highly appreciated in the industrial sector. The pigments with wolframite structure, besides the electrical and photoluminescent properties, present different colors that modify according to the chromophore ion present in its constitution. In the present work, pigments with Ni1-xCuxWO4 composition (x = 0.00, 0.01, 0.02, 0.04 and 0.08) were synthesized by the chemical precipitation and coprecipitation method and calcined at different temperatures. The pigments were characterized by X-ray diffraction (XRD), infrared spectroscopy, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), photoluminescence spectroscopy and UV-Visible spectroscopy. Then, they were incorporated into the transparent glaze and applied to ceramic pieces. All pigments synthesized were crystalline, nanometric, single-phase, with a wolframite-type structure. The pigments showed fluorescence with broad emission band in the violet-blue region. According to the diffuse reflectance data and the CIEL * a * b * parameters, pigment color shades ranged from greenish gray to orange gray in pigments doped with copper ion calcined at 900 oC. The colorimetric analysis of the enamelled ceramic pieces showed in the CIE chromaticity diagram a color variation from yellow to green, both with low color saturation. The synthesis method precipitation and coprecipitation and the calcination process, showed to be efficient to production of oxides with a wolframite structure, besides presenting colors and optical properties suitable for use as ceramic coating
Keywords: Wolframatos; Pigmentos Sintéticos; Fotoluminescência; Revestimentos Cerâmicos; Wolframites; Synthetics Pigments; Photoluminescence; Ceramic Coatings; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA